Between Assistance and Anxiety: How AI Impacts Writing Stress among EFL English Literature Majors - Widhya Putriana (Lembaga Pengembangan Kinerja Dosen, 2025)
This research explores the dual impact of Artificial Intelligence (AI) on the academic writing experiences of English Literature students learning English as a Foreign Language (EFL). AI tools like ChatGPT, Grammarly, and QuillBot are commonly used for grammar correction and sentence construction. These tools are integrated into students' writing processes, providing valuable assistance in refining their written work. However, their psychological effects, particularly in terms of emotional and ethical implications, have not been sufficiently explored in previous research. This study employed a qualitative phenomenological approach, utilizing Interpretative Phenomenological Analysis (IPA), to examine the experiences of ten final-year EFL students who actively use AI tools for academic writing. Through semi-structured interviews, the research identified three major themes: reduced technical stress, heightened dependency on AI tools, and ethical concerns about authorship. The findings suggest that while AI tools act as cognitive scaffolds, aiding students by improving fluency and reducing the burden of technical writing tasks, they also introduce psychological challenges. These challenges include increased dependency on the tools and concerns about the authenticity of their work, raising questions about academic integrity and self-efficacy. This study sheds light on the complex relationship between AI as an assistive technology and its potential to cause writing anxiety and dependency. By emphasizing both the positive and negative psychological impacts of AI, the study contributes to the growing body of literature on AI in education. It calls for the development of pedagogical frameworks that balance AI literacy, emotional resilience, and ethical considerations to ensure responsible and effective use of AI in academic contexts.